The presentation of self in everyday life - Goffman, Erving (Doubleday, 1959)
A notable contribution to our understanding of ourselves. This book explores the realm of human behavior in social situations and the way that we appear to others. Dr. Goffman uses the metaphor of theatrical performance as a framework. Each person in everyday social intercourse presents himself and his activity to others, attempts to guide and cotnrol the impressions they form of him, and employs certain techniques in order to sustain his performance, just as an actor presents a character to an audience. The discussions of these social techniques offered here are based upon detailed research and observation of social customs in many regions.